Experimental Hyalohyphomycosis by Purpureocillium lilacinum: Outcome of the Infection in C57BL/6 Murine Models - de Sequeira, Danielly C. M.; Menezes, Rodrigo C.; Oliveira, Manoel M. E.; Antas, Paulo R. Z.; De Luca, Paula M.; Oliveira-Ferreira, Joseli de; Borba, Cintia de Moraes (Frontiers in Microbiology, 2017)
Purpureocillium lilacinum is a filamentous, hyaline fungus considered an emerging pathogen in humans. The aim of our study was to evaluate the outcome of hyalohyphomycosis in C57BL/6 murine models inoculated with two clinical P. lilacinum isolates (S1 and S2). Each isolate was inoculated in mice randomly distributed in immunocompetent (CPT) and immunosuppressed (SPS) groups. Mice were evaluated at day 7, 21 and 45 after inoculation for histopathological analysis, recovery of fungal cells and immunological studies. Histological analysis showed scarce conidia-like structures in lung tissue from CPT mice and a lot of fungal cells in SPS mice inoculated with S2 compared to mice inoculated with S1. The maximum recovery of fungal cells was seen in CPT mice inoculated with both isolates at day 7th, but with mean significantly higher in those inoculated with S2 isolate. Phenotypical characterization of T cells showed TCD8+ lymphocytes predominance over TCD4+ in immunosuppressed mice infected and control groups. We also observed higher percentages of the central and effector memory/effector phenotype in CPT mice infected with S2 strain, especially in TCD8+ in the initial period of infection. Regulatory T cells showed higher percentages in immunosuppressed, predominantly after the acute phase. Our results showed that the P. lilacinum is a fungus capable to cause damages in competent and immunosuppressed experimental hosts. Furthermore, S2 isolate seems to cause more damage to the experimental host and it was possible to identify different cellular subsets involved in the mice immune response.